Impact of obstructive sleep apnoea on cognitive function in multiple sclerosis: A longitudinal study. (13th August 2020) - McNicholas, Nuala; Russell, Audrey; Nolan, Geraldine; Tubridy, Niall; Hutchinson, Michael; Garvey, John Francis; McGuigan, Christopher
Abstract: Cognitive impairment (CI) and fatigue are common in people with multiple sclerosis (MS), with well‐known profound effects on quality of life. Sleep disorders, including obstructive sleep apnoea (OSA), are also common in MS patients. The presence of CI has previously been shown to strongly correlate with OSA diagnosed using polysomnography in MS. Treatment of OSA has not previously been investigated as a potential modality to improve cognition in MS patients. Therefore, we sought to investigate the potential effects of OSA treatment on both cognitive function and fatigue in MS patients. Twenty‐three participants with MS reporting significant fatigue were enrolled. CI was assessed by the Brief International Cognitive Assessment in MS and the 3‐second Paced Auditory Serial Addition Test. All participants underwent overnight polysomnography to assess for possible OSA. Cognitive and fatigue measures were repeated in those subsequently treated for OSA and in a comparative untreated sample. Seven participants (30%) had a diagnosis of OSA based on an apnoea–hypopnea index greater than 5 per hour, with no correlation between the presence of CI and OSA. Verbal learning at follow‐up assessment was seen to improve significantly in those treated for OSA, compared with those who were not treated for a sleep disorder. This small study demonstrates the potential for OSA treatment to improve verbal learning in people with MS, larger studies are indicated to further investigate the potential for cognitive and fatigue improvement in people with MS through treatment of comorbid OSA.